Demographic and clinical influences on emotion prosody recognition - Martin Simcik; Ross Andel; Jan Pavlik; Petr Marusic; Jana Amlerova; Jakub Hort (Frontiers in Psychology, 2026)
Introduction Emotion recognition from speech prosody is a complex cognitive ability that depends on the functional integrity of a distributed neuronal network and may be shaped by demographic, clinical and lifestyle factors. The Terrapino mobile application was developed as a tool to promote cognitive health, but its digital infrastructure and methodologically rigorous design also render it suitable for research purposes including a comprehensive battery to assess Alzheimer’s disease risk factors, as well as measures of perceived stress, metamemory, and prosody recognition. Methods We analyzed data from 2,858 adult Terrapino users aged 18–103 years (median = 60 years) to identify correlates of emotional prosody recognition across a demographically, clinically and lifestyle-diverse population. Participants completed an emotion prosody recognition test comprising 25 audio recordings in which professional actors conveyed one of five basic emotions (fear, sadness, anger, disgust and happiness) solely through vocal intonation. Results Consistent with previous research, age, sex, education, hearing problems, subjective cognitive complaints and the number of comorbidities were associated with performance, with several predictors significant in at least one age group. However, other hypothesized factors, such as alcohol consumption, depression, perceived stress, average hours of sleep, or living alone, did not show significant associations with performance in prosody recognition. Discussion Together, these findings identify the main demographic and health factors associated with emotional prosody recognition across the adult lifespan and indicate that, in this large appbased cohort, performance is associated with age and health-related factors rather than with the lifestyle variables examined.